When archaeology meets communities : impacting interactions in Sicily over two eras (Messina, 1861-1918) - Crisà, Antonino (Archaeopress Publishing Ltd, 2018)
'When Archaeology Meets Communities' examines the history of 19th-century Sicilian archaeology through the archival documentation for the excavations at Tindari, Lipari and nearby minor sites in the Messina province, from Italy's Unification to the end of the First World War (1861-1918).